2001
DOI: 10.1042/0264-6021:3560621
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin interacts with mitochondria and induces cytochrome c release

Abstract: Although triorganotins are potent inducers of apoptosis in various cell types, the critical targets of these compounds and the mechanisms by which they lead to cell death remain to be elucidated. There are two major pathways by which apoptotic cell death occurs: one is triggered by a cytokine mediator and the other is by a mitochondrion-dependent mechanism. To elucidate the mechanism of triorganotin-induced apoptosis, we studied the effect of tributyltin on mitochondrial function. We found that moderately low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Our structural studies reveal that the two conserved cysteine residues (Cys32 and Cys34) that constitute the putative TMT-binding site 20,21 reside at the end of the transmembrane domain close to the lipid/solvent interface, which makes these residues accessible for TMT interaction. Previous studies have shown that dialkyltin and trialkyltin compounds interact with vicinal thiol groups, resulting in cellular apoptosis, 5,74,75 lending support to the hypothesis that a direct binding of TMT may be responsible for initiating the apoptotic cascade.…”
Section: Discussionmentioning
confidence: 83%
“…Our structural studies reveal that the two conserved cysteine residues (Cys32 and Cys34) that constitute the putative TMT-binding site 20,21 reside at the end of the transmembrane domain close to the lipid/solvent interface, which makes these residues accessible for TMT interaction. Previous studies have shown that dialkyltin and trialkyltin compounds interact with vicinal thiol groups, resulting in cellular apoptosis, 5,74,75 lending support to the hypothesis that a direct binding of TMT may be responsible for initiating the apoptotic cascade.…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies have shown that cysteine and histidine residues are the primary biological ligands for organotin(IV) compounds [85] and that vicinal dithiols rather than monothiols constitute a general target for organotin(IV) [86].…”
Section: Biological Effects Of the Parents Organotin(iv) Compoundsmentioning
confidence: 99%
“…One mechanism postulated for protein-organotin interactions is the formation of covalent bonds between the tin(IV) atom and thiols present in proteins [2,17,25]. This mechanism has been corroborated by recent in vitro studies showing that vicinal dithiols rather than monothiols are responsible for mediating the biochemical effects of organotin compounds [25][26][27][28].…”
Section: Introductionmentioning
confidence: 86%
“…More importantly, vicinal cysteine residues have been implicated in the progressive dealkylation of organotin compounds in both bacteria and mammals [13,28,47,48], with a mechanism similar to the degradation of alkyllead and alkylmercury compounds [49,50]. In particular, the organotin dealkylation carried out by the dithiols of SNN-PEP shows similarities to the degradation of organomercurials into inorganic Hg(II) by organomercurial lyase (MerB) in bacteria resistant to organomercurial compounds [51][52][53][54].…”
Section: Is the Mechanism Of Dealkylation Of Organotin Compounds Simimentioning
confidence: 96%
See 1 more Smart Citation